2017
DOI: 10.18488/journal.1007/2017.7.10/1007.10.260.268
|View full text |Cite
|
Sign up to set email alerts
|

The impact of monetary strategies on economic growth: an empirical analysis for Pakistan

Abstract: The present study aims to check the long run relationship between monetary variables and gross domestic product. The study has used the yearly data for the periods of 30 years from 1983 to 2013. It is concluded that GDP is positively associated with M2, government expenditures, and inflation. While it is negatively related with interest rate, growth becomes possible with low interest rate. Investment opportunities are increased in economy. With currency appreciation, it has positive impact on growth. Domestic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Stationarity of Data-ADF and PP test were employed to check the stationarity of the data. The results are in line with Mahmood and Sial (2012), Shaheen et al, (2013), Umer (2014), Adeeb et al, (2014), Ayub and Maqbool (2015), Ahmad et al, (2016), Hussain et al, (2017), Mahmood et al, (2017), andHimayatullah (2017).…”
Section: Empirical Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Stationarity of Data-ADF and PP test were employed to check the stationarity of the data. The results are in line with Mahmood and Sial (2012), Shaheen et al, (2013), Umer (2014), Adeeb et al, (2014), Ayub and Maqbool (2015), Ahmad et al, (2016), Hussain et al, (2017), Mahmood et al, (2017), andHimayatullah (2017).…”
Section: Empirical Results and Discussionsupporting
confidence: 85%
“…The demand for money plays an important role in the formulation of monetary policy. Mahmood et al, (2017) concluded that GDP is positively linked to M2. Trade openness plays a momentous role in increasing economic growth of a country.…”
Section: Empirical Investigation Of Fiscal Monetary and Trade Policie...mentioning
confidence: 99%
“…The study finds that the lagged private sector credit growth, nominal exchange rate, and inflation have a statistically significant effect on private sector credit growth while financial innovation, interest rates, and GDP growth appear not to be important determinants of private sector credit growth. Mahmood et al (2017) have presented a time series data analysis to find the long-run relationship between money supply (M2) and Gross Domestic Product for a data set from 1983 to 2013. They have confirmed that M2, government spending and inflation rate, all have a significant positive impact on GDP, whereas interest rate has a negative impact on economic growth which concludes that low-interest rate triggers economic growth.…”
Section: The Determinants Of Domestic Credit To Private Sectorsmentioning
confidence: 99%
“…The result of this study showed that the money supply was a dominant reason for inflation. Mahmood, Waheed and Khalid (2017) estimated the effect of monetary policy on the economic growth of Pakistan. This study used time series data which covered the period from 1983 to 2013.…”
Section: Literature Reviewmentioning
confidence: 99%